The Political Movement for the Republic of Kosovo – July 2, 1990 - Agon Krasniqi (Journal of Balkan Studies)
The purpose of writing this paper is to provide new information on the political situation in Kosovo during the year 1990, with a particular focus on the political movement in Kosovo for the Republic of Kosovo. The analysis of the July 2nd event holds significant importance for Albanian historiography, marking the first major step by Albanians of Kosovo in opposing the March 1989 constitution, which had revoked Kosovo's autonomy a status initially achieved through the 1974 constitution. As a result, Kosovo was reclassified as a subject under the Serbian Republic. My study's focus on the July 2nd event aims to examine archival sources and interpret them using an analytical method, to offer a perspective on one of Kosovo’s most pivotal events in the 1990s. The objectives of the paper will focus on the political situation in Kosovo following the abolition of Kosovo's autonomy, which influenced the political developments in Kosovo during 1990. The focus will then shift to the constitutional declaration of July 2nd, the delegates, the developments during the declaration of the republic, the decisions made during the session, as well as the developments after the July 2nd event and the international reactions. This work relies heavily on archival resources from the State Agency of Kosovo Archives (ASHAK), the Municipal Archive of Kaçanik, the "Sadik Tafarshiku" Library, and the "Rilindja", "Bujku", "Bota Sot"  newspapers. In addressing this topic, my focus has been on uncovering archival sources and interpreting them. Based on this approach, I will present various archival documents, including the minutes from July 2, 1990—a historical event symbolizing the declaration of Kosovo’s republic within the framework of the Socialist Federal Republic of Yugoslavia (SFRY). This act demonstrates Kosovo’s reaction against the 1989 constitution, which revoked its autonomy, indicating Kosovo’s position as equal to the other republics within the SFRY. This reaction was marked in the hall of the Kosovo Assembly on July 2, 1990, with the participation of 114 delegates; by July 3, the final delegate was also present, bringing the total to 115 delegates who signed the declaration for Kosovo to become the seventh republic of Yugoslavia. The reason for the delay of the 115th delegate refers to extraordinary events and difficult conditions for attending the session. Thus, with the 115 signatures of the delegates of the Kosovo Assembly, Kosovo was declared a Republic of Yugoslavia, which was a success of the political movement, a success that surpassed even the declaration of autonomy in 1974.Through the use of archival sources and their scientific interpretation, we will draw key conclusions regarding the topic, helping to understand the role and significance of the July 2nd event in Kosovo’s history.